Amazing powers - Saunders, Catherine (New York : DK Publishing, 2007)
Introduces superheroes from the universes created by Marvel Comics and discusses their amazing powers, including Spider-Man, the X-Men, the Fantastic Four, and Elektra.
"Come meet the Marvel Heroes and learn all about their amazing powers."--P. [4] of cover.
Includes index.
Keywords: Comic strip characters -- Juvenile literature; Heroes -- Juvenile literature